Navigating Challenges and Opportunities in Sustainable Natural Resources Management in Long Pahangai District - Ding, Thomas; B, Jauchar; Patty, Alberto Noviano (Manunggal Halim Jaya, 2025)
Long Pahangai District, located in Mahakam Ulu Regency, East Kalimantan, has significant natural resource potential in forestry, agriculture, plantations, and ecotourism. However, this potential remains underutilized due to isolation, weak infrastructure, and ecological degradation. The importance of this research lies in discussing the limited academic attention to sustainable natural resource management (SNRM) in remote border areas that face governance and development asymmetry. Unlike previous research centered on accessible areas, this study fills the gap by examining the potential and barriers of SNRM in Long Pahangai, where indigenous ecological knowledge interacts with fragile institutional systems. This study uses a qualitative systematic literature review (SLR) using thematic content analysis of academic publications, government reports, and local initiatives. The data are categorized into thematic clusters to identify contextual patterns of sustainability. These findings reveal substantial potential, including strong traditional forest management, adaptive agroforestry practices, and the growth of community-based ecotourism. Instead, the main obstacles consist of poor transportation infrastructure, limited renewable energy capacity, ongoing deforestation, and low technology adoption. Conceptually, this research contributes to the discourse of polycentric environmental governance by positioning border areas as critical but marginalized spaces for sustainability innovation. It highlights how integrating indigenous institutions with local governments and civil society can foster ecological resilience and balance. The study recommends policy directions focused on community empowerment, decentralized renewable energy, and participatory ecotourism development. Future research should include participatory fieldwork to enrich the empirical foundation and validate the dynamics of adaptive governance in Indonesia's border regions.